Hound dog true - Urban, Linda (Boston : Sandpiper, 2011)
Mattie, a shy fifth grader, wants to hide out at her new school by acting as apprentice to her Uncle Potluck, the custodian, but her plan falls apart when she summons the courage to speak about what matters most and finds a true friend.
Bulletin of the Center for Children's Books starre
School Library Journal starred
Wilson's Children
Booklist, September 2011
Bulletin of the Center for Children's Books starre, November 2011
Horn Book, September 2011
Keywords: Bashfulness -- Juvenile fiction; Families -- Juvenile fiction; Friendship -- Juvenile fiction; Janitors -- Juvenile fiction; Moving, Household -- Juvenile fiction; Schools -- Juvenile fiction; Bashfulness -- Fiction; Family life -- Fiction; Friendship -- Fiction; Janitors -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Family life -- Fiction; Friendship -- Fiction; Janitors -- Fiction; Moving -- Fiction; School stories; Shyness -- Fiction